Impact of Total Ionizing Dose on Radio Frequency Performance of 22 nm Fully Depleted Silicon-On-Insulator nMOSFETs - Zhanpeng Yan; Hongxia Liu; Menghao Huang; Shulong Wang; Shupeng Chen; Xilong Zhou; Junjie Huang; Chang Liu (Micromachines)
In this paper, the degradation mechanism of the RF performance of 22 nm fully depleted (FD) silicon-on-insulator nMOSFETs at different total ionizing dose levels has been investigated. The RF figures of merit (the cut-off frequency fT, maximum oscillation frequency fmax) show significant degradation of approximately 14.1% and 6.8%, respectively. The variation of the small-signal parameters (output conductance (gds), transconductance (gm), reflection coefficient (|Γin|), and capacitance (Cgg)) at different TID levels has been discussed. TID-induced trapped charges in the gate oxide and buried oxide increase the vertical channel field, which leads to more complex degradation of small-signal parameters across a wide frequency range.